2015
DOI: 10.1371/journal.pone.0121473
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-HT3 Receptor on Food Intake in Fed and Fasted Mice

Abstract: BackgroundMany studies have shown that 5-hydroxytryptamine (5-HT) receptor subtypes are involved in the regulation of feeding behavior. However, the relative contribution of 5-HT3 receptor remains unclear. The present study was aimed to investigate the role of 5-HT3 receptor in control of feeding behavior in fed and fasted mice.Methodology/Principal FindingsFood intake and expression of c-Fos, tyrosine hydroxylase (TH), proopiomelanocortin (POMC) and 5-HT in the brain were examined after acute treatment with 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Moreover, (i) there was a significant difference in diarrhoea severity score between intervened and mock-treated mice at 48 and 72 h p.i, (ii) mock-treated mice had significantly more total diarrhoea output than intervened mice and (iii) Ondansetron-treatment resulted in better weight gain ( Fig 8A–8E ). The latter finding should be put in the light of observations that serotonin help control food intake [ 78 , 79 ] and that feeding behaviour in fasting mice may be related to C-fos activity in the hypothalamus and brainstem [ 80 ]. It should also be noted that RV infection activates C-fos in CNS [ 3 ], which suggests a common signalling pathway that may result in less appetite during RV illness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, (i) there was a significant difference in diarrhoea severity score between intervened and mock-treated mice at 48 and 72 h p.i, (ii) mock-treated mice had significantly more total diarrhoea output than intervened mice and (iii) Ondansetron-treatment resulted in better weight gain ( Fig 8A–8E ). The latter finding should be put in the light of observations that serotonin help control food intake [ 78 , 79 ] and that feeding behaviour in fasting mice may be related to C-fos activity in the hypothalamus and brainstem [ 80 ]. It should also be noted that RV infection activates C-fos in CNS [ 3 ], which suggests a common signalling pathway that may result in less appetite during RV illness.…”
Section: Discussionmentioning
confidence: 99%
“…Mazzola-Pomietto and colleagues [52] reported a transient inhibition of feeding (within the first hour), followed by transient hyperphagia (between 1 and 4 hr), after systemic mCPBG treatment (10 mg/kg) in food-restricted male Wistar rats, though chin-rubbing behavior may have interfered with food intake early in the session. Recently, a similar transient inhibition of acute feeding was observed following SR 57227 (a 5-HT 3 agonist) treatment in food restricted, but not fed, mice [60]. That 5-HT 3 receptor stimulation does not appear to consistently reduce feeding when given systemically may suggest differential involvement of 5-HT 3 receptors in food intake under different dietary and deprivation conditions across the hindbrain (see introduction), the ventral tegmentum, and the NAcc.…”
Section: 0 Discussionmentioning
confidence: 77%
“…We also observed that pretreatment with baclofen reversed leptin‐induced reduction of food intake in fasted mice, indicating that GABA‐B receptor might be implicated in the regulation of food intake by leptin. We have previously reported that 5‐HT 3 receptor agonist SR‐57227 significantly inhibited the food intake of fasted mice which can be blocked by 5‐HT 3 receptor antagonist ondansetron . Some evidence have shown that systematic baclofen administration can increase the food intake of animals in a dose‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%